2022
DOI: 10.3389/fonc.2022.861324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of early stage HER2-positive breast cancer patients treated with trastuzumab: A population-based real world multicenter cohort study

Abstract: IntroductionSince its introduction in standard of care, trastuzumab has revolutionized the treatment of patients with early and late stages of HER2-positive breast cancer. While the initial clinical trials were convincing and lead to major changes in practice, more knowledge on the long-term outcome and tolerability is needed. The present study was designed to assess the survival, prognostic factors and relapse patterns after the implementation of trastuzumab in a real-world cohort.MethodsAll cases of HER2-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Nevertheless, HER2 status interpretation, and subsequently, an accurate classification of BC patients, can be affected by several factors, with HER2 heterogeneity being the most important one, as documented elsewhere for other neoplasms [33,41,42]. In fact, In clinical practice, these guidelines have been used to discriminate HER2-negative BCs from HER2-positive BCs, the latter being eligible for target therapy with anti-HER2 monoclonal antibodies, such as trastuzumab, pertuzumab, and margetuximab, which are able to improve the clinical outcomes of these tumors [23][24][25][35][36][37]. However, only 20% of BCs are HER2-positive, leaving the rest with fewer treatment options, confined to endocrine therapy and/or chemotherapy with less clinical benefits and more side effects [38][39][40].…”
Section: How To Currently Establish the Her2 Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, HER2 status interpretation, and subsequently, an accurate classification of BC patients, can be affected by several factors, with HER2 heterogeneity being the most important one, as documented elsewhere for other neoplasms [33,41,42]. In fact, In clinical practice, these guidelines have been used to discriminate HER2-negative BCs from HER2-positive BCs, the latter being eligible for target therapy with anti-HER2 monoclonal antibodies, such as trastuzumab, pertuzumab, and margetuximab, which are able to improve the clinical outcomes of these tumors [23][24][25][35][36][37]. However, only 20% of BCs are HER2-positive, leaving the rest with fewer treatment options, confined to endocrine therapy and/or chemotherapy with less clinical benefits and more side effects [38][39][40].…”
Section: How To Currently Establish the Her2 Statusmentioning
confidence: 99%
“…Obviously, the ISH rejection criteria have to be applied in a rigorous fashion in all BC cases (Table 2). In clinical practice, these guidelines have been used to discriminate HER2-negative BCs from HER2-positive BCs, the latter being eligible for target therapy with anti-HER2 monoclonal antibodies, such as trastuzumab, pertuzumab, and margetuximab, which are able to improve the clinical outcomes of these tumors [23][24][25][35][36][37]. However, only 20% of BCs are HER2-positive, leaving the rest with fewer treatment options, confined to endocrine therapy and/or chemotherapy with less clinical benefits and more side effects [38][39][40].…”
Section: How To Currently Establish the Her2 Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the advent of Trastuzumab in the late twentieth century, prognosis of HER2+ breast cancer has improved significantly by measure of overall survival (OS), progressionfree survival (PFS), and recurrence-free survival [47]. However, prognosis among all patients with breast cancer with metastases to the brain remains poor, with survival of about 3-36 months [48].…”
Section: Prognosis Of Patients With Her2+ Breast Cancer With Metastas...mentioning
confidence: 99%
“…The evidence on the impact of systemic, adjuvant therapies is mainly for anti-HER2 or endocrine treatments. Studies from Canada and Sweden using data from the real-world setting found that anti-HER2 targeted agents led to survival improvements for women with HER2-positive early BC, with 5-year BC-specific survival of 93% versus 87% for patients receiving or not receiving adjuvant trastuzumab in 2006–2014, respectively [ 10 ▪ , 55 ].…”
Section: New Treatmentsmentioning
confidence: 99%